The 2016 Kaikωura Earthquake: Experiences of Safety, Evacuation, and Return for Apartment Dwellers in Te Whanganui-a-Tara, Aotearoa New Zealand. Issue 1 (March 2022) - Blake, Denise; Becker, Julia; Hodgetts, Darrin; Hope, Angela
This research explores the ways in which safety and emotion were drivers of evacuation for people residing in high-density inner-city housing in the Central Business District of Te Whanganui-a-Tara (Wellington) following the 2016 Kaikωura earthquake. Drawing predominantly on qualitative free-response answers from a survey of 803 people approximately one year after the Kaikωura earthquake, the study argues that ontological insecurity was a key driver of people's actions. Key themes identified in relation to ontological insecurity and emotional responses were the severity of the shaking and how it was experienced, the building damage, official warnings, the ongoing earthquake aftershocks, and the social actions of others. This work argues that with the ongoing growth in high-density inner-city living, disaster risk and emergency management should encompass preparedness, response, and recovery strategies that include emotional responses and social processes while valuing the specificity of inner-city living.